Porous Strained Pt Nanostructured Thin‐Film Electrocatalysts via Dealloying for PEM Fuel Cells. Issue 2 (9th December 2019) - Hwang, Chang‐Kyu; Kim, Jong Min; Hwang, Sehoon; Kim, Joo‐Hyung; Sung, Chang Hyun; Moon, Byung‐Moo; Chae, Keun Hwa; Singh, Jitendra Pal; Kim, Seung‐Hoon; Jang, Seung Soon; Lee, Seung Woo; Ham, Hyung Chul; et al.
Abstract: The exploitation of state‐of‐the‐art Pt/C electrocatalysts for polymer electrolyte membrane fuel cells (PEMFCs) is mostly limited, due to high Pt loading and durability issues caused by electrochemical instability of the carbon support in high potential regimes. In this study, the authors report that high‐compressive 3D Pt nanostructured thin films can considerably increase the catalytic activity and electrochemical durability of electrocatalysts under PEMFC device operating conditions. The nanostructure fabrication relies on the dealloying or selective leaching of solid alloys of Pt–C binary film to produce a residual 3D nanoporous thin‐film structure. A very rich structural behavior from the dealloying is shown, in which stress relief plays a governing role; the films possess a 3D structure of randomly interpenetrating ligaments and hierarchical pores with sizes between less than 50 nm and several tens of micrometers. In addition, a significant change is observed in the average lattice constant (1.55% compressive strain), which can tune the structural and electronic states of catalytic sites for enhancing the activity of the Pt electrocatalysts. Electrochemical performance of the fabricated porous strained Pt thin‐film electrocatalysts in both half‐cell and single‐cell analyses has demonstrated activity and durability superior to benchmark carbon support Pt catalysts. Abstract : Porous strained Pt nanostructure thin films are fabricated by magnetron sputtering with the O2 plasma dealloying process and they exhibit outstanding oxygen reduction reaction activity as well as electrochemical durability in polymer electrolyte membrane (PEM) fuel cells.